Empowerment of MSME crafts recommendation system with content-based filtering method on social commerce after the pandemic - Ahmad Kamal Ariffin Mohd Rus; Suaini Binti Sura; Lai Po Hung; Renita Astri; Titi Kurniati (EDP Sciences, 2023)
Since the government officially declared the end of the pandemic in Indonesia, face-to-face trading activities between buyers and traders have increased again, especially in West Sumatra province. Some traders, in addition to running their businesses offline, also continue to utilize social media as they did during the pandemic, especially in marketing activities. Therefore, the purpose of this research is to assist handicraft merchants in particular, in empowering social commerce, by understanding the behavior of recommendation systems (RS) which are specialized software for filtering in social commerce. The application of the right method determines the performance of an RS. In this discussion, the method used in RS for filtering is content-based. By applying this method, it can produce an RS that is right to support the marketing techniques of handicraft shops online, by adding complete, detailed, and uniform descriptions to each promotional photo or graphic model.